A Systematic Review and Meta-Analysis Examining Whether Changing Ovarian Sex Steroid Hormone Levels Influence Cerebrovascular Function - Skinner, Bethany D.; Davies, Rebecca J.; Weaver, Samuel R.; Cable, N. Tim; Lucas, Samuel J. E.; Lucas, Rebekah A. I. (Frontiers in Physiology, 2021)
Sex differences in cerebrovascular disease rates indicate a possible role for ovarian sex steroid hormones in cerebrovascular function. To synthesise and identify knowledge gaps, a systematic review and meta-analysis was conducted to assess how ovarian sex steroid hormone changes across the lifespan affect cerebrovascular function in women. Three databases (EMBASE, MEDLINE and Web of Science) were systematically searched for studies on adult cerebrovascular function and ovarian sex steroid hormones. Forty-five studies met pre-defined inclusion criteria. Studied hormone groups included hormone replacement therapy (HRT; n = 17), pregnancy (n = 12), menstrual cycle (n = 7), menopause (n = 5), oral contraception (n = 2), and ovarian hyperstimulation (n = 2). Outcome measures included pulsatility index (PI), cerebral blood flow/velocity (CBF), resistance index (RI), cerebral autoregulation, and cerebrovascular reactivity. Meta-analysis was carried out on HRT studies. PI significantly decreased [−0.05, 95% CI: (−0.10, −0.01); p = 0.01] in post-menopausal women undergoing HRT compared to post-menopausal women who were not, though there was considerable heterogeneity (I2 = 96.8%). No effects of HRT were seen in CBF (p = 0.24) or RI (p = 0.77). This review indicates that HRT improves PI in post-menopausal women. However, there remains insufficient evidence to determine how changing ovarian sex steroid hormone levels affects cerebrovascular function in women during other hormonal phases (e.g., pregnancy, oral contraception).